Aspectos biológicos e ecológicos do Desmodus rotundus rotundus, Chiroptera (E.Geoffroy, 1810) no Nordeste do Brasil - Odon Antão de Alencar (1977)
The biological and ecological aspects of 2,901 D.r. rotundus in 17 colonies were studied ours a period of one year. The average populations was estimated to be between 152 and 844 bats. The proportion captured varied from a maximum of 88,12% to a minimum of 26,8%. The proportion of recaptures varied from 2,95% to 81,16%. Maximum movement of the colonies was observed to be between 19,00 and 23,00 hrs. Captures were as fallows: 1,064 males leaving and 341 returning; 1,110 females leaving and 386 returning. Of the 1,383 mature males, 905 had external scrota and 478 internal testicles. Of the 1,468 females, 452 were pregnant and 1,016 were not. A total of 110 females were lactating, 128 were in estrus, 1,349 in anestrus. A total of 118 were juvenile. Nine banded bats were found to have changed colonies. The totals number of recaptures were: 658 twice, 212 three times, 74 four times, 19 five times, 7 six times and one seven times. Minimum and maximum body wights of the different groups were as follows: after feeding, non-pregnant 34,0 g to 64,8 g; prior to feeding, non-pregnant 28,9 g to 50,0 g; after feeding, pregnant 40,0 g to 65,7 g, prior to feeding, pregnant 31,0 g to 59,3 g. Number of males with external scrota after feeding 38,0 g to 50,0 g ; with external scrota, prior to feeding 27,2 g to 47,7 g; with internal scrota, after feeding 32,1 g to 47,7 g, with internal scrota, prior to feeding 25,0 g to 45,9 g. Average body wights prior to feeding was found to be 35,3 g for males and 37,8 for females. Forearm lenghts were 60,6 mm for males and 63,1 mm for females. The two habitats studied had the following relative humidity (RH) and temperature: (1) internal, 21,8°C, and 21,4°C with RH of 98% and 100%. (2) external, 28,8°C and 34,6°C with RH of 63% and 52%.